Sustainable Village Tourism Development Based on Community : Study of Sukarara Tourism Village, Central Lombok Regency - Pikrianto Pikrianto; Yustina Denik Risyanti; Hartoyo Soehari; Apri Kuntariningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the community-based sustainable tourism development in Sukarara Tourism Village, Central Lombok Regency. In the context of the NTB regional government's initiative to promote 99 tourism villages, this research employs a qualitative method with a case study approach to explore the role of the community in preserving local culture, enhancing the economy, and protecting the environment. The results of this study show that the collaboration between the community and the government in Sukarara Tourism Village has created sustainable and inclusive tourism, positively impacting both the community and the environment. The village government emphasizes the importance of preserving the ikat weaving tradition and effective environmental management, despite facing challenges related to infrastructure and human resource skills. Community involvement through Pokdarwis groups is crucial in planning and implementing tourism activities. Innovations in local product development, such as handicrafts and traditional foods, are optimized through effective training and promotion. The community also provides tourism services, including homestays and local guides, to enhance visitor experiences. Community involvement in decision-making through village meetings ensures that tourism policies reflect local needs. Environmental preservation is carried out through cleanup programs and education for tourists, while infrastructure development is improved with community participation. With a collaborative approach, Sukarara Tourism Village can become a successful example of sustainable tourism that benefits future generations.